(untitled) (Research, Society and Development, 2022)
Ozone therapy is an adjuvant and optional therapeutic treatment with ozone administration. In dentistry it is promising for its biological attributes such as antimicrobial effect, analgesia, anti-inflammatory property and tissue resting. The objective of this work was to carry out an integrative review of the use of ozone as an auxiliary therapy in endodontic treatment. Searches for articles were performed in the following databases: Scielo and Pubmed. Inclusion criteria published between 2016 to 2021, with online access, were considered. The search keys used were: Ozone and root canal and endodontic and Ozone and root canal. 88 articles were found in the selected databases, after screening by title and abstract 26 studies were selected, among the 26 articles, 17 of them were selected for full reading, 11 articles were excluded for not being available for full reading in PDF and 6 studies were included for this integrative review. The ways of using ozone in the present study were ozonized water and ozone gas. The use of ozone has positive results, in most studies in both forms, when compared to the use only of conventional irrigants.